Internationalization as a development strategy for small & medium-sized enterprises (SMEs) on the example of Raptor - Rutkowski Krzysztof (My University, 2008)
The basic aim of this thesis is to analyze the nature and impact of internationalization as SME development strategy, to identify the internationalization strategy of the “Raptor” company and to evaluate its impact on this company competitive position. The specific goals of this thesis are as follows: 1. Analysing the nature and economic importance of the SME sector. 2. Presenting the drivers, origins and impact of the internationalization of economic activity. 3. Characterising patterns, strategies, structures and impact of the SME internationalization. 4. Indentifying and evaluating the international strategy of the “Raptor” company. 5. Recommending future directions for the international strategy of “Raptor”. In the first chapter, I will present the characteristics and the criteria of SME identification. Later on I will present the input that SMEs provide into the economy of the European Union and into the Polish economy. In the end of this chapter I will compare the strengths and weaknesses of SMEs in Poland and in the EU. The second chapter will be focused on the internationalization. In the first part I will present the drivers of this phenomenon. Further on into the chapter I will discuss the origins of internationalization and its economic and social impacts. The chapter will conclude with the analysis of the institutions that regulate international activities. The third chapter will be about the internationalization of small and medium-sized enterprises. In the beginning I will show the patterns of internationalization of SMEs, followed by basic internationalization strategies and structures. In the end of this chapter I will present the opportunities and threats that internationalization may pose for SMEs. The fourth chapter will include the analysis of drivers, origins and phases of the internationalization of the “Raptor” company, the identification and evaluation of its to-date internationalization strategy as well as recommendations for future directions of this firm development based on the internationalization. I will utilize both desk research and field research in order to access primary and secondary data. The secondary data will include: books, reports, papers, internet web-sites, and the “Raptor” records and informational materials. The primary data will be obtained through semi-structured interview with the co-owner of the company analyzed.
Internacjonalizacja jako strategia rozwoju małych i średnich przedsiębiorstw (MSP) na przykładzie firmy „Raptor”
Keywords: internacjonalizacja przedsiębiorstwa; małe i średnie przedsiębiorstwa; rozwój przedsiębiorstwa; strategia; działalność gospodarcza; small and medium companies; business development; strategy; economic activity; internationalization of the enterprise